WEAPONIZING WORDS: WAR METAPHORS AND PUBLIC PERSUASION IN AL JAZEERA’S ISRAEL BOYCOTT DISCOURSE - Fathurrohim, Ilham Hanif; Nur, Tajudin; Krisnawati, Ekaning (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
Alongside the Tūfānu 'l-ʔAqṣā or 'Al-Aqsa Flood' operation, the phenomenon of boycotting Israel was once again discussed around the world. This boycott caused a decrease in revenue for several Israeli companies in Muslim countries, including Arab countries. Media as one of the institutions that participate in shaping public image and opinion on various matters certainly has a hand in the spread of boycott propaganda. Moreover, media such as Al Jazeera which has a wide reach and high credibility in Arab countries, play a significant role in the spread of boycott propaganda. One of the features used by the media, which can construct a person's concepts and arguments fundamentally, as well as persuade, is metaphor. Moreover, one of the metaphors that is widely used in various fields, especially politics, to attract public attention and create influence is the war metaphor. This study aims to describe the conceptual metaphor of war and to reveal the ideology behind the use of war metaphors in the Israel boycott discourse on the Al Jazeera Arabic online newspaper. This study reveals that the war metaphor is not merely linguistic, but also expresses Al Jazeera’s ideological stance, shaping public perception of the Israeli–Palestinian conflict, especially regarding the boycott. The news data source was obtained from the Al Jazeera Arabic online newspaper since the Tūfānu ‘l-ʔAqṣā or 'Al-Aqsa Flood' operation from 7 October 2023 to 31 May 2024. This qualitative descriptive study analyzes metaphors through three stages of Critical Metaphor Analysis: metaphor identification using MIP, interpretation using conceptual metaphor theory, and explanation. A total of 74 metaphorical expressions were identified from 12 war-related lexemes. All war metaphors frame the boycott positively by highlighting its urgency, power, effectiveness, and impact, especially within the context of Palestinian resistance. These findings indicate that Al Jazeera aligns with the ideology of resistance and promotes it through metaphorical framing. The significance of this study lies in its contribution to understanding how ideological war metaphors influence public perception and mobilize political action. It sheds light on the rhetorical strategies of Arab media in shaping resistance discourse, offering broader insight into the role of language in geopolitical narratives.